Marketing Performance in MSMEs Culinary Sector: The Effect of Market Orientation, Product Innovation, and Competitive Advantage - Itaul Masaroh; Herni Justiana Astuti (Danadyaksa: Post Modern Economy Journal, 2026)
This study aims to analyze the influence if market orientation, product innovation, and competitive advantage on marketing performance in culinary micro, small, and medium enterprises in Bukateja Diistriict, Purbaliingga Regency. This study employed a quantitative approach and purposive sampling, with 120 culinary business owners as respondents. The criteria for respondents in this study are MSMEs operating in Bukateja Diistriict, Purbaliingga Regency, that have conducted promotional activities or product innovations in their culinary businesses and have been operating for at least two years. Data were collected through online questionnaires using Likert-scale measures. The analysis technique used in this study is multiple linear regression analysis supported by the statistical software SPSS 27. The instruments in this study have passed the validity and reliability test, as well as the classical assumption test. The results of the study show that market orientation, product innovation, and competitive advantage have a positive and significant influence on marketing performance. These findings highlight the importance of strengthening market orientation, enhancing product innovation, and building a competitive advantage to improve marketing performance